Analisis Faktor-Faktor Yang Mempengaruhi Ekspor Udang Indonesia Terhadap Enam Negara Tujuan - Pramastya, Andiena Fitri (Jurnal Manajemen Akuntansi (JUMSI), 2023)
Shrimp is one of the fishery commodities that have a major contribution in the international market. Export is one of the parameters that is very important to consider, so that a country can know how much its economic growth. This study aims to see how Indonesian shrimp exports in destination countries and what factors affect the performance of Indonesian shrimp exports to destination countries. This analysis using Gravity Model method using panel data and already using Chow test and Hausman test and multicolinearity test. Shrimp Commodity Data Used time series data from 2001-2020. In this study, it was found that Indonesian shrimp exports were significantly influenced by the GDP of the export destination country, economic distance, shrimp prices and inflation. The destination country'S GDP, shrimp prices, and economic distance have a significant negative relationship, while inflation has a significant positive relationship.